2011
DOI: 10.1037/a0023819
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cognitive development.

Abstract: The potential effect of gender on intellectual abilities remains controversial. The purpose of this research was to analyze gender differences in cognitive test performance among children from continuous age groups. For this purpose, the normative data from 7 domains of the newly developed neuropsychological test battery, the Evaluación Neuropsicológica Infantil [Child Neuropsychological Assessment] (Matute, Rosselli, Ardila, & Ostrosky-Solis, 2007), were analyzed. The sample included 788 monolingual children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
67
1
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 8 publications
13
67
1
12
Order By: Relevance
“…Generally, girls outperform boys on language and other verbal tasks, while boys tend to perform better on tasks that require spatial abilities (Levine, Huttenlocher, Taylor, & Langrock, 1999;Linn & Petersen, 1985;Mann, Sasanuma, Sakuma, & Masaki, 1990;Strand, Deary, & Smith, 2006;Voyer, 2011). However, contrasting results have been reported as well (Ardila, Rosselli, Matute, & Inozemtseva, 2011;Strand et al, 2006). Surprisingly, in previous publications, the authors of the developmental NEuroPSYchological assessment second edition (NEPSY-II), the instrument used in our study, have not reported on the relationship between gender and neuropsychological functioning on the NEPSY-II (Korkman et al, 2001(Korkman et al, , 2013.…”
Section: Introductioncontrasting
confidence: 57%
“…Generally, girls outperform boys on language and other verbal tasks, while boys tend to perform better on tasks that require spatial abilities (Levine, Huttenlocher, Taylor, & Langrock, 1999;Linn & Petersen, 1985;Mann, Sasanuma, Sakuma, & Masaki, 1990;Strand, Deary, & Smith, 2006;Voyer, 2011). However, contrasting results have been reported as well (Ardila, Rosselli, Matute, & Inozemtseva, 2011;Strand et al, 2006). Surprisingly, in previous publications, the authors of the developmental NEuroPSYchological assessment second edition (NEPSY-II), the instrument used in our study, have not reported on the relationship between gender and neuropsychological functioning on the NEPSY-II (Korkman et al, 2001(Korkman et al, , 2013.…”
Section: Introductioncontrasting
confidence: 57%
“…Some of them have worked a period of time before they joined campus, so their life experience is more abundant. Although Baer's study showed a gender equality in creative potential [14], the males advantage in the creative achievements of the real world is clearly visible, and they always have outperform females in mathematics and science [15]. Karwowski [16] also supported that male performance is better than female in creativity and clarified the reasons for it.…”
Section: The Influence Of Gender On Postgraduates' Creativitymentioning
confidence: 99%
“…Thus, if initially speaking of real advantages that boys recorded in several disciplines such Mathematics or Sciences (Physics, Chemistry, Biology), more recent research has shown that reality is not fully sustaining that idea [2,3], considering there are no major differences between the cognitive capacities or the competences of the students of both genres, being based on social constructs, which involve a primary orientation, often determined by the family and community, towards certain school disciplines associated with the gender dimension.…”
Section: Problem Statementmentioning
confidence: 99%